Species diversity and phylogenetic analysis of Heliconia spp. collections of Purwodadi Botanic Garden (East Java, Indonesia) inferred by rbcL gene sequences - LIA HAPSARI; TRIMANTO TRIMANTO; DIDIK WAHYUDI (Society for Indonesian Biodiversity, 2019)
Abstract. Hapsari L, Trimanto, Wahyudi D. 2019. Species diversity and phylogenetic analysis of Heliconia spp. collections of Purwodadi Botanic Garden (East Java, Indonesia) inferred by rbcL gene sequences. Biodiversitas 20: 1266-1283. Heliconia L. is a single genus in the family Heliconiaceae, with approximate consists of 200 species. It has wide morphological variations among and within species which led to problems in species identification. Species diversity and phylogenetic analysis using morphology and rbcL marker subjected to 17 Heliconia spp. living collections of Purwodadi Botanic Garden (PBG) have been conducted. The rbcL gene located in chloroplast genome is one of appropriate proposed marker for plant barcoding assessment. This study aimed to study morphology and genetic variability of the PBG Heliconiaceae collections, to confirms the species name for a more accurate identity record and to reveal the diversity and phylogenetics of the species. Morphological characterization showed high variability among Heliconia species, which included 3 subgenera (Heliconia, Stenochlamys, and Griggsia) and 1 hybrid. Each species possessed unique morphological characteristics. The common morphological characters which distinguished among and within Heliconia species includes leaf form, inflorescence type, and bract characteristics. Key to the Heliconia species examined is presented in this paper. However, molecular confirmation using rbcL sequences showed high conservation level (0.932) and low genetic variability. About 656 nucleotides were monomorphic and 33 positions were polymorphic which comprised 18 singleton variable sites and 15 parsimony informative sites. Twelve haplotypes were produced with haplotype diversity value 0.8952. Pairwise distance analysis shows that they were shared high similarity of rbcL sequences with very low genetic distance (0.022 to 0.000). The topology of phylogenetic tree resulted by Neighbour-Joining algorithm has the best grouping and be able to explain the relationship among species of Heliconia, although supported by low bootstrap (65). It was separated into two clades following its subgen. classification. Clade 1 consists of subgen. Heliconia and Griggsia; while clade 2 consists of subgen. Heliconia and Stenochlamys; also hybrid species. Further, separation of deeper branchings (section) was inconsistent and unclear. Upon this study, rbcL marker was considered too conserved thus less valuable for phylogenetic analysis at lower taxa among and within Heliconia spp. However, rbcL was suggested to distinguish at higher level taxa between closely related genus and above.